2009
DOI: 10.1089/thy.2008.0153
|View full text |Cite
|
Sign up to set email alerts
|

Association of XRCC1 Polymorphisms and Risk of Differentiated Thyroid Carcinoma: A Case–Control Analysis

Abstract: The XRCC1 194Trp variant allele may be associated with increased risk of DTC, while the XRCC1 399Gln variant allele may be associated with decreased risk of DTC. The utility of XRCC1 haplotypes in predicting DTC risk deserves further investigation with direct haplotype measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 17 publications
0
56
0
Order By: Relevance
“…Tumor histology was assessed by pathologists at each participating institution. The median time from diagnosis to recruitment was 4 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Personal and clinical data, such as family history of thyroid cancer and What's new?…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor histology was assessed by pathologists at each participating institution. The median time from diagnosis to recruitment was 4 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Personal and clinical data, such as family history of thyroid cancer and What's new?…”
Section: Subjectsmentioning
confidence: 99%
“…9 Moreover, there is evidence that gene-gene 10,11 and gene-environment interactions 12,13 modulate individual susceptibility. In this scenario, both carefully designed candidate-gene association studies [14][15][16] and genome-wide association studies (GWAS) [17][18][19][20] have been used to identify susceptibility variants for DTC.…”
mentioning
confidence: 99%
“…There are also some case-control studies conducted to explore the association of SNPs of XRCC1 and thyroid cancer risk (Zhu et al, 2004;Chiang et al, 2008;Siraj et al, 2008;Akulevich et al, 2009;Ho et al, 2009;Sigurdson et al, 2009;Fard-Esfahani et al, 2011;García-Quispes et al, 2011;Ryu et al, 2011). However, the results were not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of database searches, 33 papers were retrieved, of which five full-text articles were ultimately included in our meta-analysis (Chiang et al, 2008;Ho et al, 2009;Fard-Esfahani et al, 2011;Ryu et al, 2011;Santos et al, 2012). A flow chart representing the study selection process is shown in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%